2014
DOI: 10.3233/jrs-140622
|View full text |Cite
|
Sign up to set email alerts
|

Preventive intervention for iron deficiency anaemia in a high risk population

Abstract: BACKGROUND: Iron deficiency anaemia (IDA) is a common nutritional problem. OBJECTIVE: To determine the effect of nutritional education and supplemental iron administration on the prevalence of IDA in Arab infants. METHODS: Three hundred and ten infants were randomized alternately into two groups. Mothers (n = 143) in the control group received standard information on prevention of IDA and mothers in the intervention group (n = 144) received extensive information on the importance of an iron-rich diet. Data was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Frequency of anaemia was lower in infants who received ≥6 months of iron medication according to mothers’ reports, and in infants breastfed for ≥6 months”. 17 In our study, we also found that families who received information about IDA and iron medicine and duration of consumption, used the iron medicine more.…”
Section: Discussionsupporting
confidence: 64%
“…Frequency of anaemia was lower in infants who received ≥6 months of iron medication according to mothers’ reports, and in infants breastfed for ≥6 months”. 17 In our study, we also found that families who received information about IDA and iron medicine and duration of consumption, used the iron medicine more.…”
Section: Discussionsupporting
confidence: 64%
“…Three studies followed participants starting at or close to their birth, 2,7,20 1 study enrolled participants by 30 days of age, 16 and 1 followed participants starting at about 4 months. 8 Participants in the U.S. study were mostly White, 2 participants in the multinational study were all White, 16 participants in the study from Iceland had Icelandic parents, 20 and participants in the study from Israel were Arab and about 61% were from low-income families. 8 Isomura et al 7 did not report demographic information.…”
Section: Risk Of Biasmentioning
confidence: 98%
“…Ten articles, published between 1990 and 2019, examined the relationships of ever compared with never consuming human milk, and different durations of any human milk consumption, with iron status from birth to 24 months. [1][2][3][7][8][9]12,16,20,23 No evidence was identified that met the inclusion criteria to examine different durations of exclusive human milk consumption before the introduction of infant formula or different intensities, proportions, or amounts of human milk consumed by mixed-fed infants.…”
Section: Iron Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency of anaemia was lower in infants who received iron medication ≥ 6 months and in infants breastfed for ≥ 6 months. After this study various questions were raised regarding the strategies of preventing iron deficiency anaemia in infancy [7] .…”
Section: Dietary Involvement In Prevention Of Anaemiamentioning
confidence: 99%